Implementation of a Teaching at the Right Level Approach (TaRL) in the Merdeka Curriculum to Improve Chemistry Learning Outcomes at X.3 SMAN 5 Palembang - Rosa, Yuni Hartati Eliya; Nawawi, Effendi; Sari, Novitalia Ablinda (Jurnal Pendidikan dan Pembelajaran Kimia, 2024)
. This research aims to improve the chemistry learning outcomes of X.3 students at SMA Negeri 5 Palembang through the TaRL approach. The type of data used is quantitative and qualitative data. Qualitative through direct observation, observation instruments and documentation. Meanwhile, quantitative is obtained through calculating the percentage of pre-cycle, cycle I and II using the criteria for achieving learning objectives (KKTP). Student learning outcomes 4 category: Proficient, Competent, Developing and Needs Guidance. After the research, there was an increase in the learning outcomes of students in the category requiring guidance from the pre-cycle, decreasing from 12 students (34%), to 4 students (11%) in cycle I, and 0 students (0%) in cycle II. On Developing category pre-cycle 12 students (26%), becoming 6 students (17%) in cycle I, and 3participantstudents (9%) in cycle II. For the proficient category, there was an increase starting from 8 students (23%) in the pre-cycle, to 10 students (29%) in cycle I, and 17 students (34%) in cycle II. The same thing happened in the Advanced category where the increase started from pre-cycle 6 students (17%), to 15 students (43%) in cycle I, and 20participantstudents (57%) in cycle II. Keywords: Chemistry, Learning Outcomes, Merdeka Curriculum, TaRL.DOI: 10.23960/jppk.v13.i1.2024.10